(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The effective teaching of microbiology to students requires a combination of theoretical instruction and practical laboratory experience. This article explores the essential equipment needed to teach microbiology in educational settings, with an emphasis on the tools necessary for studying microorganisms, performing experiments, and maintaining laboratory safety. The goal is to provide a comprehensive overview of the critical instruments and apparatus required to ensure a successful and interactive learning environment for microbiology students.